A Flexible probability model for reliability data: The extended half-normal distribution with further results - Eman Khorsheed; Hugo Salinas; Hassan Bakouch (Kuwait Journal of Science)
Recent years have shown growth in the potential applications of extensions of skew and half-normal distributions. In this paper, we provide and study, in detail, a flexible and extended class of such distributions. The developed distribution has a scale parameter and two shape parameters. We carry out a Monte Carlo simulation with Maximum Likelihood Estimation to assess the performance of this technique for a variety of parameter values. The power of the distribution is demonstrated with real applications using two reliability data sets. The results reveal that the proposed distribution can produce a better fit than several other distributions.